Prevalensi dan Gambaran Karakteristik Dismenorea pada Remaja - Wahyuni, Wahyuni; Zulfahmi, Ulfah (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2021)
Background: Dysmenorrhea is a gynecological condition that most commonly occurs in women of childbearing age. Dysmenorrhea is defined as a paiful sensation, cramping in the lower abdoment, and is often accompanied by other symptoms, such as sweating, headache, nausea, vomiting, diarrhea, and shaking. All of this happens right before or during menstruation. Primary dysmenorrhea complaints are often experienced by young women under 25 years old. Dysmenorrhea often results in disruption of activities and social relationships. Pondok Pesantren Putri Ar-Rohmah is a special Islamic boarding school for female students aged 13-18 years. At this age, primary dysmenorrhea complaints often occur. The activities of the students are also very far from the words of heavy activity, they only recite the recitation, memorization and formal schooling which is very lacking in physical activity. Objective: The purpose of this study was to determine the prevalence and description of the characteristics of primary dysmenorrhoea in adolescents at Islamic Boarding School Putri Ar-Rohmah Ngawi. Method: This research was quantitative research with descriptive observational methods. Result: From the study, the prevalence of primary dysmenorrhoea in adolescents in Islamic boarding schools was 83.1%. The highest characteristic of dysmenorrhoea is caused by lack of physical activity, namely 54.2% of respondents are less active and 5.8% of respondents have sedentary behavior. Conclusion: The characteristic description that most influences the occurrence of dysmenorrhoea in students is inadequate physical activity. Meanwhile, the description of the characteristics of body mass index, age of menarche, menstrual cycle, and menstrual duration are not the main characteristics that cause dysmenorrhea in respondents.